2018
DOI: 10.1088/1741-2552/aaae1d
|View full text |Cite
|
Sign up to set email alerts
|

Patterning of functional human astrocytes onto parylene-C/SiO2substrates for the study of Ca2+dynamics in astrocytic networks

Abstract: The significance of this work is to demonstrate how patterning hNT astrocytes replicates spatio-temporal clustering of Ca signalling that is observed in vivo but not in dissociated in vitro cultures. We therefore highlight the importance of the structure of astrocytic networks in determining ensemble Ca behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 37 publications
(59 reference statements)
2
24
0
Order By: Relevance
“…Visualisation of the astrocyte Ca 2+ signalling was evaluated using time-lapse microscopy and a fluorescent Ca 2+ probe using a method we developed previously (see Raos et al for a detailed description of the methods used [11]). Briefly, astrocytes were labelled with Fluo-4 (1 μm in 1% FBS/Fluorobrite DMEM) for 30 min at 37°C and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Visualisation of the astrocyte Ca 2+ signalling was evaluated using time-lapse microscopy and a fluorescent Ca 2+ probe using a method we developed previously (see Raos et al for a detailed description of the methods used [11]). Briefly, astrocytes were labelled with Fluo-4 (1 μm in 1% FBS/Fluorobrite DMEM) for 30 min at 37°C and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Hughes et al demonstrated patterning of LUHMES neuronal networks by first patterning a template of glial-like stem cells on parylene-C/SiO 2 substrates [10]. More recently, human neurons and astrocytes, which were derived from the NTera2.D1 (hNT/NT2) cell line, have been patterned by Unsworth et al, Jordan et al, and Raos et al [7, 9, 11, 12]. The NT2 (hNT) cell line provides a readily available source of neurons and astrocytes that are more applicable to human physiology than primary cells of non-human origin [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NT2-Astrocytes (NT2A). NT2A cells were generated as described previously (19) and were cultured on uncoated 25 cm 2 culture flasks in DMEM/F12 at 37 ˚C in 20% O2, 5% CO2.…”
Section: For Experimental Conditions Requiring Fetal Bovine Serum (Fbmentioning
confidence: 99%
“…Therefore, the efficient derivation of functional astrocytes from differentiating stem cells is rapidly becoming the focus of many research labs, as it is seen as a crucial step in understanding brain function in health and disease. Furthermore, from a neuroengineering perspective, facilitation of astrocyte procurement enables multiple studies, investigating neural circuit patterning (Delivopoulos et al, 2009;Delivopoulos and Murray, 2011;Unsworth et al, 2011;Raos et al, 2018), and development (Clarke and Barres, 2013) both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%